- Perbandingan McKenzie dan Isometric Neck Exercise terhadap Keseimbangan pada Forward Head Posture: Studi pada Karyawan Pengguna Komputer - Munawaroh, Naela; Sugiarto, Stephanie Indrawati; Wahyudati, Sri; Setiawati, Erna (Medica Hospitalia : Journal of Clinical Medicine, 2022)
BACKGROUND: The increasing use of computers in the current era is accompanied by an increase in the prevalence of poor posture due to the use of computers in fixed and inappropriate positions for a long time. This has the potential to cause changes in posture and body alignment such as forward head posture. McKenzie neck exercise and isometric neck exercise are considered to help maintain normal spinal alignment and improve body posture. OBJECTIVE: To compare the effect of McKenzie and Isometric Neck Exercise to balance in forward head posture METHOD: This study is an experimental study with a quasi-experimental pre and post-test design. Research subjects are computer users at RSUP dr Kariadi Semarang who suffer from forward head posture. A total of 24 research subjects were divided into group 1 (n=12) who received McKenzie neck exercise and group 2 (n=12) who received isometric neck exercise. Allocation was done by simple randomization. Each group did the exercise 12 times for 4 weeks with a frequency of 3 times per week. Balance assessment using the mCTSIB (Modified Clinical Test of Sensory Integration on Balance) questionnaire. Data analysis used Shapiro Wilk, Mann Whitney, independent t-test and paired t-test. RESULT: The demographic data of the sample in this study did not show any significant difference in either group 1 and 2. There was a significant improvement in condition 1 (balance on a flat bed with open eyes) in group 1 (p = 0.025). Significant results were also obtained in condition 2 (balance on a flat bed with closed eye) in group 2 (p = 0.041). There was no significant difference in the analysis of the two intervention groups. The McKenzie group did not provide a greater improvement in balance when compared to the isometric neck exercise group. CONCLUSION: McKenzie exercise is not superior to isometric neck exercise in improving balance